Distributed Economic Dispatch Based on Finite-Time Double-Consensus Algorithm of Integrated Energy System - Yang, Jun; Du, Jianhai (Frontiers in Energy Research, 2022)
To reduce the operating cost and enhance the energy utilization efficiency of the integrated energy system (IES), an economic dispatch algorithm is proposed based on finite-time double-consensus. First, an economic dispatch model of IES under two modes of operation, islanded and grid-connected, is constructed considering energy transmission losses. After that, the optimal improved incremental cost and power output allocation of the IES can be found out in finite time. The proposed algorithm contains two finite-time consistency protocols simultaneously that can solve the optimal values of the incremental cost of electricity and heat of integrated energy system, solving the strong coupling problem of multi-energy systems. The proposed algorithm not only has a faster convergence rate but also enables switching freely between the two operation modes. In addition, a distributed method for quickly discovering the total system power mismatch is proposed in the process of algorithm solving. The finite-time convergence of the proposed algorithm is demonstrated. Finally, the IES simulation based on the IEEE 30-node power system and the Bali 32-node thermal system is established. The analysis of the simulation results shows that the algorithm proposed in this paper is effective.